THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF QUALITY COSTS AND EFFORTS TO IMPROVE PRODUCT QUALITY (A CASE STUDY AT PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK) - Fadilah, Sri; Meilia, Najwa; Lisdayani, Nopi (Yayasan Nuraini Ibrahim Mandiri, 2024)
The use of herbal medicine products has seen a decline in trust due to a lack of scientific evidence proving their effectiveness, perceptions of unsafe or unhygienic ingredients, and the negative stigma that views herbal medicine as an outdated form of treatment. However, herbal medicine is believed to have fewer side effects due to the use of natural ingredients passed down through generations. Despite this, many herbal products with chemical ingredients and easily accessible imported herbal products negatively impact the development of traditional herbal medicines, especially in small-scale industries that lack standardization in line with Good Traditional Medicine Manufacturing Practices. Quality costs are the expenses incurred to perform all activities related to the development of product quality. These costs include prevention, appraisal, internal failure, and external failure costs. Quality costs serve as an indicator of product quality success and competitive advantage. PT Industri Jamu dan Farmasi Sido Muncul, the largest herbal medicine producer in Indonesia, strives to improve product quality through consistent supervision and quality enhancement. This study employs a case study method to analyze the relationship between the implementation of quality costs and efforts to improve product quality at PT Sido Muncul. The findings indicate that effective quality cost control contributes to product quality improvement, reduces defective products, lowers costs, and increases profits. Sido Muncul emphasizes the use of science, technology, and research to create high-quality products. Thus, significant investments in product quality improvement provide the company with a competitive advantage, enabling it to maintain and increase its market share. Keywords: Cost Concept, Product Quality, Quality Costs